Nonlinear image processing - Mitra, Sanjit Kumar; Sicuranza, Giovanni L. (Academic Press series in communications, networking and multimedia., 2001)
This state-of-the-art book deals with the most important aspects of non-linear imaging challenges. The need for engineering and mathematical methods is essential for defining non-linear effects involved in such areas as computer vision, optical imaging, computer pattern recognition, and industrial automation challenges. * Presents the latest developments in a variety of filter design techniques and algorithms * Contains essential information for development of Human Vision Systems (HVS) * Provides foundations for digital imaging and image capture technology.